2015
DOI: 10.1007/s00438-014-0984-4
|View full text |Cite
|
Sign up to set email alerts
|

Host genetic variations in glutathione-S-transferases, superoxide dismutases and catalase genes influence susceptibility to malaria infection in an Indian population

Abstract: Antioxidant enzymes can contribute to disease susceptibility or determine response to therapy in individuals with malaria. Genetic variations due to polymorphisms in host genes encoding antioxidant enzymes such as glutathione S-transferases-theta, mu, pi (GSTT, GSTM, GSTP), superoxide dismutases (SOD) and catalase (CAT), may therefore, influence inter-individual response to malaria pathology and propensity of infection caused by Plasmodium vivax (Pv) and Plasmodium falciparum (Pf). Therefore, using polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 74 publications
0
8
0
5
Order By: Relevance
“…Ранее нами показано, что у больных такими клещевыми инфекциями, как клещевой энцефалит и иксодовый клещевой боррелиоз, в случае носительства делеции гена GSTM1(0/0) фермента глутатион-Sтрансферазы наблюдаются тератозооспермия и повышенная частота встречаемости цитогенетических аберраций в соматических клетках [4][5][6]. Однако в литературе мы не нашли исследований, посвященных изучению способности инфекции, вызывающей ГАЧ, индуцировать тератозооспермию или/и цитогенетические нарушения у больных людей.…”
Section: Teratozoospermia and Karyopathologiсal Abnormalities Of Bloounclassified
See 1 more Smart Citation
“…Ранее нами показано, что у больных такими клещевыми инфекциями, как клещевой энцефалит и иксодовый клещевой боррелиоз, в случае носительства делеции гена GSTM1(0/0) фермента глутатион-Sтрансферазы наблюдаются тератозооспермия и повышенная частота встречаемости цитогенетических аберраций в соматических клетках [4][5][6]. Однако в литературе мы не нашли исследований, посвященных изучению способности инфекции, вызывающей ГАЧ, индуцировать тератозооспермию или/и цитогенетические нарушения у больных людей.…”
Section: Teratozoospermia and Karyopathologiсal Abnormalities Of Bloounclassified
“…ального времени с использованием амплификатора Терцик (Россия). ДНК для ПЦР выделяли из проб венозной крови [4,6]. Продукты амплификации и рестрикции ампликонов разделяли в горизонтальном 3% агарозном геле с применением камеры для горизонтального электрофореза ЕС 12-13 («Биоком», Москва, Россия).…”
Section: материал и методыunclassified
“…It has also been reported that peptides disrupting the interaction of Gas and b2AR block erythrocyte invasion by Pf parasites in vitro (Harrison et al, 2003). Genetic screening of individuals for the factors affecting erythrocyte phase of infection Saadi et al, 2013;Fernandes et al, 2015) in endemic areas, may provide new insight into the possible mechanisms that may explain the varied susceptibility of individuals to malarial infection. Reports that are available suggest that adenosine receptors play a major role in cellular functions by coupling to G proteins, although several effects independent of G-proteins have also been reported (Fredholm et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Studies have shown that the T allele has been associated with increased levels of CAT when compared to the C allele (Forsberg et al, ; Galecki et al, ; Hebert‐Schuster et al, ; Kodydková et al, ). Additionally, this polymorphism has been associated with many pathological conditions, such as: HCC (Ezzikouri et al, ), breast cancer (Ahn et al, ), asthma (Mak et al, ), rheumatoid arthritis (Bohanec Grabar et al, ), and susceptibility to malaria (Fernandes et al, ).…”
Section: Introductionmentioning
confidence: 99%